Evaluation method for new and old asphalt fusion of recycled asphalt mortar

Through in-situ technology and rheology tests, combined with the Frecher distance evaluation method, the problem of mismatch between the new and old asphalt fusion tests in the existing technology and the actual situation is solved, and the accurate evaluation of the degree of fusion of new and old asphalt in the recycled asphalt mortar is achieved, and the performance of the recycled asphalt mixture is improved.

CN119880652AActive Publication Date: 2025-04-25HOHAI UNIV +1

Patent Information

Application Number
CN202510360853.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-26
Publication Date
2025-04-25
Estimated Expiration
2045-03-26

AI Technical Summary

Technical Problem

The fusion test of new and old asphalt in the prior art does not match the actual situation. The extraction test has a negative impact on the fusion evaluation of new and old asphalt. The micro-test is expensive and difficult to operate, and it is impossible to effectively evaluate the degree of fusion of new and old asphalt in regenerated asphalt mortar.

Method used

In situ technology is adopted, regenerated asphalt mortar with different degrees of fusion is obtained by heating oil-rich RAP fines and fresh asphalt and then insulated at 165°C, and then stirring and pulping under the same conditions. Rheology performance indicators were obtained using the bending beam rheology test, low temperature main curves were drawn, and the similarity between the main curves of different fusion degrees and the fully fusion main curves were evaluated by the Frecher distance.

Benefits of technology

Effectively evaluate the degree of fusion between new and old asphalt in recycled asphalt mortar, avoiding the problem of mismatch between tests and actual conditions in the prior art, improving the accuracy and efficiency of fusion evaluation of new and old asphalt, and promoting the improvement of the performance of recycled asphalt mixture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119880652A_ABST
    Figure CN119880652A_ABST
Patent Text Reader

Abstract

An evaluation method for new and old asphalt fusion of recycled asphalt mortar comprises the following steps: firstly, pulping oil-rich RAP fine materials subjected to refined separation and new asphalt, obtaining partially fused recycled asphalt mortar with different fusion degrees on site, and preparing completely fused recycled asphalt mortar for comparison; secondly, obtaining low-temperature rheological indexes at different temperatures by adopting a bending beam rheological test; drawing a low-temperature main curve according to the obtained low-temperature rheological indexes based on a time-temperature equivalence principle; and finally, evaluating the similarity between the low-temperature main curve of the mortar with different fusion degrees and the completely fused standard curve by adopting the Frechet distance, thereby serving as an evaluation method for new and old asphalt fusion of the recycled asphalt mortar. According to the method, the fusion degree of the new and old asphalt in the recycled asphalt mortar is evaluated through an in-situ technology, and the problems that an existing new and old asphalt fusion simulation test is not matched with the actual situation, an extraction test has negative effects on new and old asphalt fusion evaluation, and a microscopic test is high in price and not easy to operate are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of detection and evaluation of the physical properties of new and old asphalt in regenerated asphalt mortar, and in particular to a method for evaluating the fusion of new and old asphalt in regenerated asphalt mortar. Background Art

[0002] At present, the utilization rate of solid waste is still relatively low, and the comprehensive utilization level of bulk solid waste urgently needs to be further improved, shifting from "low-efficiency, low-value, and scattered utilization" to "high-efficiency, high-value, and large-scale utilization."

[0003] Asphalt pavement regeneration technology has been widely used in road engineering, playing an important role in repairing pavement performance and resolving the comprehensive utilization of large amounts of solid waste. To transform asphalt pavement regeneration technology from "low efficiency, low value, and scattered utilization" to "high efficiency, high value, and large-scale utilization," the efficiency of asphalt pavement regeneration needs to be improved. Currently, the main factors restricting the dosage of RAP materials in factory-mix hot regeneration are the variability of RAP and the degree of fusion between new and old asphalt. Studies have shown that the variability of RAP materials can be effectively controlled through fine separation technology. The finely separated RAP coarse material has low variability and low surface asphalt content, and the performance of the recycled asphalt mixture produced is no different from that of hot-mix asphalt mixture. However, the proportion of RAP fine material (oil-rich RAP fine material) after separation is high, and the surface asphalt content is high (up to 13%). The existing addition method cannot be effectively applied, and large-scale accumulation will cause land waste and environmental pollution. At present, the accumulated RAP fines can be treated by pre-mixing oil-rich RAP fines with new asphalt in a certain proportion and then adding them to the mixture mixing tank for production. However, due to the inconsistent sources of RAP fines, the fusion time of the aged asphalt on its surface and the new asphalt is different. However, in the actual production process, due to the efficient linkage between the pulping equipment and the mixing plant, the production time of a batch of mixture in the mixing plant is generally 70-80s. The production efficiency of the recycled asphalt mortar needs to match the production of the mixing plant. Therefore, it is urgent to evaluate whether the asphalt material used for pulping can quickly and effectively penetrate into the deep layer of the aged asphalt on the RAP surface, that is, how to evaluate the fusion of new and old asphalt in the recycled asphalt mortar.

[0004] Existing technologies typically use layered extraction, new-to-old asphalt fusion simulations, and microscopic tests such as AFM and SEM to evaluate the degree of fusion between new and old asphalt. However, the solvents used in layered extraction tests and the heating process during recovery can affect asphalt properties. Simulations of new-to-old asphalt fusion cannot fully replicate actual construction conditions, and microscopic tests are expensive and difficult to perform. Summary of the Invention

[0005] Technical problems solved: In view of the problems in the prior art such as the mismatch between the simulated new and old asphalt fusion test and the actual situation, the negative impact of the extraction test on the evaluation of the fusion of new and old asphalt, and the high cost and difficulty of operation of the microscopic test, the present invention aims at the demand for the fusion effect of new and old asphalt during the production of regenerated asphalt mortar, and proposes a method for evaluating the fusion of new and old asphalt in regenerated asphalt mortar. The method can evaluate the degree of fusion of new and old asphalt in the regenerated asphalt mortar through in-situ technology, avoiding the problems existing in the existing evaluation methods.

[0006] Technical solution: A method for evaluating the fusion of new and old asphalt in recycled asphalt mortar, with the following steps:

[0007] Step 1: heating the oil-rich RAP fine material to 165° C., heating the new asphalt to 160° C., adding the heated new asphalt to the heated oil-rich RAP fine material, and maintaining the temperature at 165° C. to obtain a mixture;

[0008] Step 2: Obtain partially fused recycled asphalt mortars with different fusion degrees: Stir the mixture to prepare slurry at 165° C. According to the preparation process of the on-site recycled asphalt mortar, set at least three groups of slurrying conditions, each with a different stirring speed and stirring time, to produce at least three partially fused recycled asphalt mortars with different fusion degrees to obtain different samples;

[0009] Step 3: Prepare a fully fused recycled asphalt mortar: perform an extraction test on an amount of oil-rich RAP fine material equal to that in step 1 to obtain recycled asphalt and recycled aggregate, heat the recycled asphalt to 160°C, then add an amount of new asphalt equal to that in step 1, stir evenly, and fully blend; then heat the recycled aggregate to 165°C, add the fully fused recycled asphalt and new asphalt, and stir evenly at 165°C to obtain a fully fused recycled asphalt mortar;

[0010] Step 4: Using a bending beam rheological test (BBR) to obtain the rheological performance indicators of the partially fused samples with different fusion degrees prepared in step 2 and the fully fused recycled asphalt mortar prepared in step 3, the rheological performance indicator is the low-temperature stiffness modulus, and the low-temperature range is -12°C to -27°C;

[0011] Step 5: Draw a low-temperature master curve based on the rheological performance indicators of step 4;

[0012] Step 6: Use the Fleche distance to evaluate the similarity between the master curves of different fusion degrees and the master curve of complete fusion. The smaller the Fleche distance, the closer the fusion degree of the recycled asphalt mortar is to complete fusion, and the better the fusion degree.

[0013] Preferably, the oil-rich RAP fine material in step 1 is RAP with a particle size of less than 3 mm after fine separation, and the new asphalt is 70# matrix asphalt.

[0014] Preferably, the mass ratio of the oil-rich RAP fines to the new asphalt in step 1 is 8:2.

[0015] Preferably, three groups of pulping conditions are set in step 2, the first group of stirring speed is 200 RPM, time is 15 min; the second group of stirring speed is 500 RPM, time is 10 min; the third group of stirring speed is 800 RPM, time is 8 min; the stirring condition in step 3 is stirring speed 200 RPM, time is 15 min.

[0016] Preferably, the test method for the bending beam rheological test in step 4 adopts the asphalt bending creep stiffness modulus test method in section T0627-2011 of the Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering JTG E20-2011.

[0017] Preferably, the test temperatures of the bending beam rheological test are -12°C, -15°C, -18°C, -21°C, -24°C and -27°C, the loading times are 8, 15, 30, 60, 120 and 240 s respectively, and the initial test load is 980 mN±50 mN.

[0018] Preferably, in step 5, the Sigmoid empirical model is used to fit the low-temperature master curve of the rheological performance index. The calculation expression of the Sigmoid empirical model is as follows (1):

[0019] (1)

[0020] Where a, b, d, and g are regression coefficients;

[0021] E * is the low-temperature stiffness modulus, MPa, obtained from step 4;

[0022] f red The calculation expression is as follows (2):

[0023] (2)

[0024] In this experiment, f red is defined as the reduction time, f is the test time in step 4, s;

[0025] is the temperature shift factor, and the calculation expression is as follows (3):

[0026] (3)

[0027] Where T is the actual test temperature in step 4, °C;

[0028] T0 is the reference temperature, °C;

[0029] C1 and C2 are fitting parameters.

[0030] Based on the time-temperature equivalence principle, the present invention parallel-shifts stress relaxation modulus curves obtained at different temperatures along a logarithmic time axis and superimposes and couples them into a smooth curve, namely, a low-temperature master curve.

[0031] Preferably, the reference temperature is -15°C.

[0032] Preferably, in step 6, the Fréchet distance is used to evaluate the similarity between the master curves of different fusion degrees and the fully fused master curve, as follows:

[0033] Step 1: Obtain the low-temperature stiffness modulus master curve E of the fully integrated recycled asphalt mortar * C , as shown in the following formula (4):

[0034] E * C ={(t1,E * C (1)), (t2,E * C (2)), …, (t n ,E * C (n)),…, (t N ,E * C (N))} (4)

[0035] Where 1-N is the serial number of the sampling points on the fully fused master curve, and N is a natural number greater than 2;

[0036] n is a natural number between 1 and N;

[0037] t n is the time of the nth sampling point, s;

[0038] E * C (n) is t n Corresponding low-temperature stiffness modulus, MPa;

[0039] t N is the time of the Nth sampling point, s;

[0040] E * C (N) is t N Corresponding low-temperature stiffness modulus, MPa;

[0041] Step 2: Obtain the low-temperature stiffness modulus master curve E of partially fused recycled asphalt mortar* P , as shown in the following formula (5):

[0042] E * P ={(t1, E * P (1)), (t2, E * P (2)), …, (t m , E * P (m)),…, (t M , E * P (M))} (5)

[0043] Where 1-M is the serial number of the sampling point on the partially fused master curve, and M is a natural number greater than 2;

[0044] m is a natural number between 1 and M;

[0045] t m is the time of the mth sampling point, s;

[0046] E * P (m) is t m Corresponding low-temperature stiffness modulus, MPa;

[0047] t M is the time of the Mth sampling point, s;

[0048] E * P (M) is t M Corresponding low-temperature stiffness modulus, MPa;

[0049] Step 3: Calculate the distances between the sampling points on the main curves of the low-temperature stiffness modulus of the fully fused and partially fused recycled asphalt mortars to obtain the distance matrix D, as shown in the following formula (6):

[0050] (6)

[0051] Where, , 1≤n≤N, 1≤m≤M;

[0052] Step 4: Find d in the distance matrix D mn The maximum value d max With the minimum value d min , set the initial target distance f=d min , and set the loop interval ;

[0053] Step 5: Binarize the distance matrix D to obtain the binary matrix D', as shown in the following formula (7):

[0054] (7)

[0055] Where, , 1≤n≤N, 1≤m≤M;

[0056] Step 6. Find a path R in the binary matrix D' that satisfies the following conditions: The starting point of R is d' 11 , the end point is d' MN ; The path passes through point d' mn After that, the next passing point can only be d' (m+1)n 、d' m(n+1) and d' (m+1)(n+1) One of the; the value of all points in the path R must be 1;

[0057] Step 7. If no path that meets the conditions is found in step 6, reset the target distance to f+r, and then loop through steps 5 and 6. The relationship between the number of loops x and the target distance is as follows: loop 1, target distance f; loop 2, target distance f+r; loop 3, target distance f+2r; ...; loop x, target distance f+(x-1)r, see Table 1 for details; if the target distance f+(x-1)r of the path that meets the conditions is found in step 6 in the xth loop, proceed to the next step;

[0058] Table 1 Relationship between cycle number and target distance

[0059]

[0060] Step 8. The Fréchet distance F=f+(x-1)r of the main curves of the low-temperature stiffness modulus of the fully fused and partially fused recycled asphalt mortar.

[0061] Beneficial effects: The present invention starts from the oil-rich RAP fine material pulping technology that improves the factory-mixed hot-recycled RAP dosage, and evaluates the degree of fusion of new and old asphalt in the regenerated asphalt mortar through in-situ technology. On the one hand, it avoids the problem that the quality of the regeneration agent is uneven due to the inability to accurately evaluate the degree of fusion of new and old asphalt, and there are multiple weak interfaces in the regenerated asphalt mixture after the fusion of new and old asphalt, which in turn brings about the problems of insufficient low-temperature crack resistance and water stability of the regenerated asphalt mixture; on the other hand, it avoids the problems that the existing simulation of the fusion of new and old asphalt tests does not match the actual situation, the negative impact of the extraction test on the evaluation of the fusion of new and old asphalt, and the high price and difficulty of operation of the microscopic test, and provides an effective way to judge the degree of fusion of new and old asphalt in on-site rapid pulping. BRIEF DESCRIPTION OF THE DRAWINGS

[0062] Figure 1This is a flow chart of an evaluation method for fusion of new and old asphalt in recycled asphalt mortar according to the present invention;

[0063] Figure 2 Schematic diagram of the low-temperature master curve of an embodiment of the present invention. DETAILED DESCRIPTION

[0064] The following will clearly and completely describe the technical solutions in the embodiments of the present invention in conjunction with the drawings in the present invention. It should be understood that the embodiments described are only some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention. The specific embodiments described here are only used to explain the present invention and are not used to limit the present invention.

[0065] like Figure 1 As shown in FIG, a method for evaluating the fusion of new and old asphalt in recycled asphalt mortar is provided, and the steps are as follows:

[0066] Step 1: heating the oil-rich RAP fine material to 165° C., heating the new asphalt to 160° C., adding the heated new asphalt to the heated oil-rich RAP fine material, and maintaining the temperature at 165° C. to obtain a mixture;

[0067] Step 2: Obtain partially fused recycled asphalt mortars with different fusion degrees: Stir the mixture to prepare slurry at 165° C. According to the preparation process of the on-site recycled asphalt mortar, set at least three groups of slurrying conditions, each with a different stirring speed and stirring time, to produce at least three partially fused recycled asphalt mortars with different fusion degrees to obtain different samples;

[0068] Step 3: Prepare a fully fused recycled asphalt mortar: perform an extraction test on an amount of oil-rich RAP fine material equal to that in step 1 to obtain recycled asphalt and recycled aggregate, heat the recycled asphalt to 160°C, then add an amount of new asphalt equal to that in step 1, stir evenly, and fully blend; then heat the recycled aggregate to 165°C, add the fully fused recycled asphalt and new asphalt, and stir evenly at 165°C to obtain a fully fused recycled asphalt mortar;

[0069] Step 4: Using a bending beam rheological test to obtain the rheological performance indicators of the partially fused samples with different fusion degrees prepared in step 2 and the fully fused recycled asphalt mortar prepared in step 3, the rheological performance indicator is the low-temperature stiffness modulus, and the low-temperature range is -12°C to -27°C;

[0070] Step 5: Draw a low-temperature master curve based on the rheological performance indicators of step 4;

[0071] Step 6: Use the Fleche distance to evaluate the similarity between the master curves of different fusion degrees and the master curve of complete fusion. The smaller the Fleche distance, the closer the fusion degree of the recycled asphalt mortar is to complete fusion, and the better the fusion degree.

[0072] As one of the preferred embodiments of the present invention, the oil-rich RAP fine material in step 1 is RAP with a particle size of less than 3 mm after fine separation, and the new asphalt is 70# matrix asphalt.

[0073] As one of the preferred embodiments of the present invention, the mass ratio of the oil-rich RAP fines to the new asphalt in step 1 is 8:2.

[0074] As one of the preferred embodiments of the present invention, three groups of pulping conditions are set in step 2, the first group of stirring speed is 200 RPM, time is 15 min; the second group of stirring speed is 500 RPM, time is 10 min; the third group of stirring speed is 800RPM, time is 8 min; the stirring conditions in step 3 are stirring speed of 200 RPM, time is 15 min.

[0075] As one of the preferred embodiments of the present invention, the test method of the bending beam rheological test in step 4 adopts the asphalt bending creep stiffness modulus test method of section T0627-2011 in the test procedures for asphalt and asphalt mixtures in highway engineering JTG E20-2011.

[0076] As one of the preferred embodiments of the present invention, the test temperatures of the bending beam rheological test are -12°C, -15°C, -18°C, -21°C, -24°C and -27°C, the loading times are 8, 15, 30, 60, 120 and 240 s respectively, and the initial test load is 980 mN±50 mN.

[0077] As one of the preferred embodiments of the present invention, in step 5, the Sigmoid empirical model is used to fit the low-temperature master curve of the rheological performance index. The calculation expression of the Sigmoid empirical model is as follows (1):

[0078] (1)

[0079] Where a, b, d, and g are regression coefficients;

[0080] E * is the low-temperature stiffness modulus, MPa, obtained from step 4;

[0081] f red The calculation expression is as follows (2):

[0082] (2)

[0083] In this experiment, f red It is defined as the reduction time, f is the test time in step 4, s;

[0084] is the temperature shift factor, and the calculation expression is as follows (3):

[0085] (3)

[0086] Where T is the actual test temperature in step 4, °C;

[0087] T0 is the reference temperature, °C;

[0088] C1 and C2 are fitting parameters.

[0089] As one of the preferred embodiments of the present invention, the reference temperature is -15°C.

[0090] As one of the preferred embodiments of the present invention, the Fréchet distance is used in step 6 to evaluate the similarity between the master curves of different fusion levels and the fully fused master curve, as follows:

[0091] Step 1: Obtain the low-temperature stiffness modulus master curve E of the fully integrated recycled asphalt mortar * C , as shown in the following formula (4):

[0092] E * C ={(t1,E * C (1)), (t2,E * C (2)), …, (t n ,E * C (n)),…, (t N ,E * C (N))} (4)

[0093] Where 1-N is the serial number of the sampling points on the fully fused master curve, and N is a natural number greater than 2;

[0094] n is a natural number between 1 and N;

[0095] t n is the time of the nth sampling point, s;

[0096] E * C (n) is t n Corresponding low-temperature stiffness modulus, MPa;

[0097] tN is the time of the Nth sampling point, s;

[0098] E * C (N) is t N Corresponding low-temperature stiffness modulus, MPa;

[0099] Step 2: Obtain the low-temperature stiffness modulus master curve E of partially fused recycled asphalt mortar * P , as shown in the following formula (5):

[0100] E * P ={(t1, E * P (1)), (t2, E * P (2)), …, (t m , E * P (m)),…, (t M , E * P (M))} (5)

[0101] Where 1-M is the serial number of the sampling point on the partially fused master curve, and M is a natural number greater than 2;

[0102] m is a natural number between 1 and M;

[0103] t m is the time of the mth sampling point, s;

[0104] E * P (m) is t m Corresponding low-temperature stiffness modulus, MPa;

[0105] t M is the time of the Mth sampling point, s;

[0106] E * P (M) is t M Corresponding low-temperature stiffness modulus, MPa;

[0107] Step 3: Calculate the distances between the sampling points on the main curves of the low-temperature stiffness modulus of the fully fused and partially fused recycled asphalt mortars to obtain the distance matrix D, as shown in the following formula (6):

[0108] (6)

[0109] Where, , 1≤n≤N, 1≤m≤M;

[0110] Step 4: Find d in the distance matrix D mn The maximum value d max With the minimum value d min , set the initial target distance f=d min , and set the loop interval ;

[0111] Step 5: Binarize the distance matrix D to obtain the binary matrix D', as shown in the following formula (7):

[0112] (7)

[0113] Where, , 1≤n≤N, 1≤m≤M;

[0114] Step 6. Find a path R in the binary matrix D' that satisfies the following conditions: The starting point of R is d' 11 , the end point is d' MN ; The path passes through point d' mn After that, the next passing point can only be d' (m+1)n 、d' m(n+1) and d' (m+1)(n+1) One of the; the value of all points in the path R must be 1;

[0115] Step 7: If no path that meets the conditions is found in step 6, reset the distance to f+r, and then repeat steps 5 and 6. The relationship between the number of cycles x and the target distance is shown in Table 1. If the target distance f+(x-1)r of the path that meets the conditions is found in step 6 in the xth cycle, proceed to the next step.

[0116] Step 8. The Fréchet distance F=f+(x-1)r of the main curves of the low-temperature stiffness modulus of the fully fused and partially fused recycled asphalt mortar.

[0117] Specific application examples are as follows:

[0118] Example 1

[0119] This embodiment provides a method for evaluating the fusion of new and old asphalt in recycled asphalt mortar, and the steps are as follows:

[0120] Step 1: preheat the oil-rich RAP fine material and new asphalt. The oil-rich RAP fine material after fine separation (sourced from G205 in Linyi City, Shandong Province, after crushing and screening by fine separation equipment, the particle size is 0-3 mm, and the oil-rich content is 11.7 wt%) is heated to 165°C in an oven. The new asphalt, i.e. 70# matrix asphalt (provided by Nantong Tongsha Asphalt Technology Co., Ltd., model is Shuanglong 70# matrix asphalt) is heated to 160°C in an oven. First, add the heated oil-rich RAP fine material to a 5L sample preparation barrel, and then add the heated 70# matrix asphalt. The mass ratio of the two is 8:2. Place the sample preparation barrel in a heating jacket with an insulation temperature of 165°C. Then immerse the variable speed torque tester stirring paddle in the material, and the distance between the paddle and the bottom of the sample preparation barrel is 2 cm.

[0121] Step 2: Obtain partially fused recycled asphalt mortars with varying degrees of fusion. The mixtures were stirred and slurried at 165°C. Three slurrying conditions were set: 200 RPM stirring, 15 min fusion (Sample 1); 500 RPM stirring, 10 min fusion (Sample 2); and 800 RPM stirring, 8 min fusion (Sample 3).

[0122] Step 3: Prepare a fully integrated recycled asphalt mortar as a control. Based on the oil content of the oil-rich RAP fines, calculate the asphalt and aggregate masses in the oil-rich RAP fines. Then, perform extraction tests on the oil-rich RAP fines to recover an equal mass of recycled asphalt and aggregate. Heat the recycled aggregate to 160°C, then add the same amount of fresh asphalt as in Step 1. Stir in a stirrer at 160°C and 200 RPM for 15 minutes to achieve complete integration. Heat the recovered recycled aggregate to 165°C, mix with the fully integrated recycled asphalt and fresh asphalt, and add the mixture to a 5L sample preparation bucket. Place the sample preparation bucket in a heating jacket maintained at 165°C. Submerge the variable speed torque tester's stirring paddle into the material, with the paddle 2 cm from the bottom of the sample preparation bucket. Stir at 200 RPM for 15 minutes to obtain a fully integrated sample.

[0123] Step 4: The fusion test was conducted using the bending beam rheology test (BBR). The test method followed T0627-2011 of the "Test Procedure for Asphalt and Asphalt Mixtures in Highway Engineering" (JTG E20-2011). BBR test samples were prepared for each of the four recycled asphalt mortars. The bending beam rheology test method is as follows:

[0124] (1) Prepare and assemble the BBR standard test piece mold. The mold is made of aluminum plate. The internal length of the mold is: 127mm±2.0mm, thickness is 6.35mm±0.05mm, and width is 12.70mm±0.05mm (BBR standard test mold);

[0125] (2) Clean the mold, apply a layer of petroleum-based grease on the inner surface of the three long metal parts of the mold, use the grease to stick the plastic sheet to the metal, assemble the mold, and pour four types of recycled asphalt mortar (sample 1, sample 2, sample 3 and fully fused sample) at 165°C into the four molds respectively;

[0126] (3) Cool at room temperature for 45-60 min, and cut the asphalt mortar sample that is higher than the top of the mold after cooling;

[0127] (4) Place the cooled mold in a cooling room or cooling water before demoulding to ensure that the specimen does not deform during demoulding;

[0128] (5) Demolding. After demolding, place the specimen in a constant temperature bath that reaches the test temperature. After maintaining the constant temperature for 60 min ± 5 min, place the specimen on the bracket for testing, and maintain the constant temperature bath temperature within ± 0.1 °C of the test temperature.

[0129] The test conditions were set as follows: BBR test temperatures were -12°C, -15°C, -18°C, -21°C, -24°C, and -27°C; the loading times were 8, 15, 30, 60, 120, and 240 s, respectively; and the initial test load was 980 mN ± 50 mN.

[0130] The test results are shown in Table 2 below:

[0131] Table 2 BBR test results (taking sample 3 as an example, others as Figure 2 shown)

[0132]

[0133] Step 5: Use the Sigmoid empirical model to fit the low-temperature master curve of the low-temperature stiffness modulus. The calculation expression of the Sigmoid empirical model is shown in the following formula (1):

[0134] (1)

[0135] Where a, b, d, g are regression coefficients, and E* is the low-temperature stiffness modulus, MPa. red The original definition is the reduced frequency, the unit is Hz, this test uses the test time instead, the unit is s, f red It is obtained by the following formula (2).

[0136] (2)

[0137] Where f is the test time in step 4, s;

[0138] is the temperature shift factor, and the calculation expression is as follows (3):

[0139] (3)

[0140] Where T is the actual test temperature, °C;

[0141] T0 is the reference temperature, °C;

[0142] C1 and C2 are fitting parameters.

[0143] Step 6: When establishing the master curve, select -15°C as the reference temperature and use the Williams-Landel-Ferry (WLF) equation to shift the test data at other temperature points toward the reference temperature. Using the nonlinear least squares method in an Excel 2003 data table, the parameters in the model and the displacement factors at each temperature can be obtained simultaneously (see Table 3). The master curve of each asphalt can then be plotted. Figure 2 shown.

[0144] Table 3 Master curve model parameters

[0145]

[0146] Step 7: Calculate the Fréchet distance between the master curves of the low-temperature stiffness modulus of fully fused and partially fused recycled asphalt mortars to evaluate the degree of fusion of each regenerated asphalt mortar. A computer-friendly discrete Fréchet distance algorithm is used to characterize the distance between the master curves of the low-temperature stiffness modulus of fully fused and partially fused recycled asphalt mortars. The smaller the Fréchet distance, the greater the similarity between the two curves, and the closer the degree of fusion of the recycled asphalt mortar is to complete fusion.

[0147] The details are as follows:

[0148] (1) Obtain the main curve E of the low-temperature stiffness modulus of the fully integrated recycled asphalt mortar * C , as shown in the following formula (4):

[0149] E * C ={(t1,E * C (1)), (t2,E * C (2)), …, (t n ,E * C (n)),…, (t N ,E * C (N))} (4)

[0150] Where 1-N is the serial number of the sampling points on the fully fused master curve, and N is a natural number greater than 2;

[0151] n is a natural number between 1 and N;

[0152] t n is the time of the nth sampling point, s;

[0153] E * C (n) is t n Corresponding low-temperature stiffness modulus, MPa;

[0154] t N is the time of the Nth sampling point, s;

[0155] E * C (N) is t N Corresponding low-temperature stiffness modulus, MPa;

[0156] (2) Obtain the main curve E of the low-temperature stiffness modulus of partially fused recycled asphalt mortar * P , as shown in the following formula (5):

[0157] E * P ={(t1, E * P (1)), (t2, E * P (2)), …, (t m , E * P (m)),…, (t M , E * P (M))} (5)

[0158] Where 1-M is the serial number of the sampling point on the partially fused master curve, and M is a natural number greater than 2;

[0159] m is a natural number between 1 and M;

[0160] t m is the time of the mth sampling point, s;

[0161] E * P (m) is t m Corresponding low-temperature stiffness modulus, MPa;

[0162] t M is the time of the Mth sampling point, s;

[0163] E *P (M) is t M Corresponding low-temperature stiffness modulus, MPa;

[0164] (3) The distances between the sampling points on the main curves of the low-temperature stiffness modulus of the fully fused and partially fused recycled asphalt mortars were calculated to obtain the distance matrix D, as shown in the following formula (6):

[0165] (6)

[0166] Where, , 1≤n≤N, 1≤m≤M;

[0167] (4) Find d in the distance matrix D mn The maximum value d max With the minimum value d min , set the initial target distance f=d min , and set the loop interval ;

[0168] (5) Binarize the distance matrix D to obtain the binary matrix D', as shown in the following formula (7):

[0169] (7)

[0170] Where, , 1≤n≤N, 1≤m≤M;

[0171] (6) Find a path R in the binary matrix D' that satisfies the following conditions: The starting point of R is d' 11 , the end point is d' MN ; The path passes through point d' mn After that, the next passing point can only be d' (m+1)n 、d' m(n+1) and d' (m+1)(n+1) One of the; the value of all points in the path R must be 1;

[0172] (7) If no path that meets the conditions is found in step 6, the distance is reset to f+r, and then steps 5 and 6 are repeated. The relationship between the number of cycles x and the target distance is shown in Table 1. If the target distance f+(x-1)r of the path that meets the conditions is found in step 6 in the xth cycle, the next step is entered.

[0173] (8) The Fréchet distance F=f+(x-1)r of the main curves of low-temperature stiffness modulus of fully fused and partially fused recycled asphalt mortar.

[0174] In this example, the Fréchet distance for Sample 1 was 0.116, for Sample 2 it was 0.0706, and for Sample 3 it was 0.1383. Therefore, the degree of fusion between the new and old asphalt in Sample 2 was closest to that of fully fused recycled asphalt mortar. Therefore, the optimal slurrying conditions were achieved with a paddle speed of 500 RPM and fusion time of 10 minutes.

[0175] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for evaluating the fusion of new and old asphalt in recycled asphalt mortar, characterized in that: Here are the steps: Step 1: heating the oil-rich RAP fine material to 165° C., heating the new asphalt to 160° C., adding the heated new asphalt to the heated oil-rich RAP fine material, and keeping the temperature at 165° C. to obtain a mixture; Step 2, obtaining partially fused recycled asphalt mortars with different fusion degrees: stirring the mixture to make pulp at 165°C, setting at least three groups of pulping conditions according to the preparation process of the on-site recycled asphalt mortar, each group having different stirring speeds and stirring times, producing at least three partially fused recycled asphalt mortars with different fusion degrees, and obtaining different samples; Step 3, prepare a completely fused recycled asphalt mortar: perform an extraction test on an amount of oil-rich RAP fine material equal to that in step 1 to obtain recycled asphalt and recycled aggregate, heat the recycled asphalt to 160°C, then add an amount of new asphalt equal to that in step 1, stir evenly, and completely blend it; then heat the recycled aggregate to 165°C, add the completely fused recycled asphalt and new asphalt, stir evenly at 165°C to obtain a completely fused recycled asphalt mortar; Step 4: Using a bending beam rheological test to obtain the rheological performance index of the partially fused samples with different fusion degrees prepared in step 2 and the fully fused recycled asphalt mortar prepared in step 3, the rheological performance index is the low-temperature stiffness modulus, and the low-temperature range is -12°C to -27°C; Step 5, drawing a low temperature master curve according to the rheological performance index of step 4; Step six: Use the Flechet distance to evaluate the similarity between the master curves of different fusion degrees and the master curve of complete fusion. The smaller the Flechet distance, the closer the fusion degree of the recycled asphalt mortar is to complete fusion, and the better the fusion degree.

2. The method for evaluating the fusion of new and old asphalt in recycled asphalt mortar according to claim 1, characterized in that: The oil-rich RAP fine material in step 1 is RAP with a particle size of less than 3 mm after fine separation, and the new asphalt is 70# base asphalt.

3. The method for evaluating the fusion of new and old asphalt in recycled asphalt mortar according to claim 1, characterized in that: In the step 1, the mass ratio of the oil-rich RAP fines to the new asphalt is 8:

2.

4. The method for evaluating the fusion of new and old asphalt in recycled asphalt mortar according to claim 1, characterized in that: In the step 2, three groups of pulping conditions are set, the first group has a stirring speed of 200 RPM and a time of 15 min; the second group has a stirring speed of 500 RPM and a time of 10 min; the third group has a stirring speed of 800 RPM and a time of 8 min; the stirring condition in step 3 is a stirring speed of 200 RPM and a time of 15 min.

5. The method for evaluating the fusion of new and old asphalt in recycled asphalt mortar according to claim 1, characterized in that: The test method for the bending beam rheological test in step 4 adopts the asphalt bending creep stiffness modulus test method of part T0627-2011 in the test procedures for asphalt and asphalt mixtures in highway engineering JTGE20-2011.

6. The method for evaluating the fusion of new and old asphalt in recycled asphalt mortar according to claim 5, characterized in that: The test temperatures of the bending beam rheological test are -12°C, -15°C, -18°C, -21°C, -24°C and -27°C, the loading times are 8, 15, 30, 60, 120 and 240 s, respectively, and the initial test load is 980 mN±50 mN.

7. The method for evaluating the fusion of new and old asphalt in recycled asphalt mortar according to claim 1, characterized in that: In the step 5, the Sigmoid empirical model is used to fit the low-temperature master curve of the rheological performance index. The calculation expression of the Sigmoid empirical model is as follows (1): (1), In the formula, a, b, d, and g are regression coefficients; E * is the low temperature stiffness modulus, MPa, obtained from step 4; f red The calculation expression is as follows (2): (2), In this method, f red It is defined as the reduction time, f is the test time in step 4, s; is the temperature shift factor, and the calculation expression is as follows (3): (3), Where T is the actual test temperature in step 4, °C; T0 is the reference temperature, °C; C1 and C2 are fitting parameters.

8. The method for evaluating the fusion of new and old asphalt in recycled asphalt mortar according to claim 7, characterized in that: The reference temperature is -15°C.

9. The method for evaluating the fusion of new and old asphalt in recycled asphalt mortar according to claim 1, characterized in that: In step 6, the Fleche distance is used to evaluate the similarity between the master curves of different fusion degrees and the fully fused master curve, as follows: Step 1: Obtain the low-temperature stiffness modulus master curve E of the fully integrated recycled asphalt mortar * C , as shown in the following formula (4): AND * C ={(t1,E * C (1)), (t2,E * C (2)), …, (t n ,AND * C (n)),…, (t N ,AND * C (N))} (4), Where 1-N is the serial number of the sampling points on the fully fused master curve, and N is a natural number greater than 2; n is a natural number between 1 and N; t n is the time of the nth sampling point, s; E * C (n) is t n Corresponding low temperature stiffness modulus, MPa; t N is the time of the Nth sampling point, s; E * C (N) is t N Corresponding low temperature stiffness modulus, MPa; Step 2: Obtain the low-temperature stiffness modulus master curve E of partially fused recycled asphalt mortar * P , as shown in the following formula (5): AND * P ={(t1, E * P (1)), (t2, E * P (2)), …, (t m , AND * P (m)),…, (t M , AND * P (M))} (5), Where 1-M is the serial number of the sampling points on the partially fused main curve, and M is a natural number greater than 2; m is a natural number between 1 and M; t m is the time of the mth sampling point, s; E * P (m) is t m Corresponding low temperature stiffness modulus, MPa; t M is the time of the Mth sampling point, s; E * P (M) is t M Corresponding low temperature stiffness modulus, MPa; Step 3: Calculate the distances between the sampling points on the main curve of the low-temperature stiffness modulus of the fully fused and partially fused recycled asphalt mortar to obtain the distance matrix D, as shown in the following formula (6): (6), In the formula, , 1≤n≤N, 1≤m≤M; Step 4: Find d in the distance matrix D mn The maximum value d max With the minimum value d min , set the initial target distance f=d min , and set the loop interval ; Step 5: Binarize the distance matrix D to obtain the binary matrix D', as shown in the following formula (7): (7), In the formula, , 1≤n≤N, 1≤m≤M; Step 6. Find a path R in the binary matrix D' that satisfies the following conditions: The starting point of R is d' 11 , the end point is d' MN ; The path passes through point d' mn After that, the next passing point can only be d' (m+1)n , d' m(n+1) and d' (m+1)(n+1) The value of all points in path R must be 1; Step 7. If no path that meets the conditions is found in step 6, reset the target distance to f+r, and then loop through steps 5 and 6. The relationship between the number of loops x and the target distance is as follows: loop 1, target distance f; loop 2, target distance f+r; loop 3, target distance f+2r; ...; loop x, target distance f+(x-1)r; if the target distance f+(x-1)r of the path that meets the conditions is found in step 6 in the xth loop, proceed to the next step; Step 8. The Frechet distance F=f+(x-1)r of the main curve of the low-temperature stiffness modulus of the fully fused and partially fused recycled asphalt mortar.

Citation Information

Patent Citations

  • Method for detection of old and new asphalt fusion degree in heat recycled asphalt mixture

    CN104406993A

  • Test method for measuring mixing degree of new asphalt and used asphalt in hot-recycled asphalt mixture

    CN106018181A

  • Method for characterizing degrees of miscibility of old and new asphalt based on dynamic moduli of mixtures

    CN109085073A

  • Method and system for determining fusion degree of recycled asphalt mixture

    CN111474157A

  • Layer-by-layer elution-based method for evaluating mixing and dissolving of new asphalt and old asphalt of thermal regeneration mixture

    CN114965098A

Cited By

  • Method for quantitatively evaluating fusion degree of new asphalt and old asphalt based on recycled asphalt mortar

    CN120594330A

  • A method for quantitatively evaluating the degree of fusion between new and old asphalt based on recycled asphalt mortar

    CN120594330B

  • Regenerated asphalt mortar dynamic heating control method and device based on torque feedback

    CN121143502A